ADHD in the Field of Education: A Systematic Literature Review (Interdisciplinary Studies Journal, 2024)
Knowing how to teach students with Attention Deficit Hyperactivity Disorder (ADHD) has been a recurring issue in the school and academic environment. In the present study, we aimed to investigate what research has shown about the teaching and learning process, taking into account the particularities of students with ADHD. Structurally, the research was built according to four questions that encompass the conceptualizations of the disorder, the learning characteristics of students with ADHD, the teaching strategies and tools used, and the teachers' reports on the subject. To apprehend them, we carried out a systematic literature review, using the Capes Periodicals Portal. as a search source, where we found 58 articles, of which 17 were selected for global data analysis. The studies reveal meaningful differences in the conceptual lines on ADHD. The results highlight the importance of using ludic and digital resources and the management of time, space and routine of students with the disorder to support their learning. However, it points to the need for more research in the area of teaching and teacher education, in order to provide subsidies for the implementation of proposals that consider the students' particularities with ADHD.
Keywords: Learning; Teaching; Students with ADHD; Literature Review